Point-of-Care Ultrasound in United States Pediatric Emergency Medicine Fellowship Programs: The Current State of Practice and Training. Issue 12 (December 2021) - Acuña, Josie; Rubin, Marina; Hahn, Barry; Das, Devjani; Kapoor, Monica; Adhikari, Srikar; Greenstein, Joshua
Abstract : Objectives: In 2015, the American Academy of Pediatrics (AAP) released a policy statement regarding point-of-care ultrasonography (POCUS) by pediatric emergency physicians, which included recommendations on education and training. In the 3 years since the AAP policy statement and its accompanying technical report were published, it is unclear which aspects of the recommendations set forth by this policy have been instituted by POCUS programs throughout the country. The objective of this study was to conduct a survey of pediatric emergency medicine (PEM) fellowship directors throughout the United States regarding the current state of education and training of POCUS in their department. Methods: We conducted an online survey of all PEM fellowship program directors in the United States between April 1, 2018, and July 31, 2018. Results: Of the 78 PEM fellowship program directors contacted, 62 (79.5%) responded. The majority reported having an ultrasound curriculum in place to educate their fellows (77%). Fellows are being taught using a variety of educational strategies. The most commonly reported barriers were lack of qualified faculty available for training (62.9%), lack of confidence or comfort in using the existing ultrasound machine(s) in their department (54.8%), and physician resistance to using new technology (50%). The majority of programs reported having processes in place for credentialing (56%) and quality assurance (72.6%). Whereas 77.4% have a system for archiving POCUS studies after they are performed, only half of the programs report utilization of middleware for their archival system. Compliance with documentation varied significantly between programs. Conclusions: Our survey results demonstrate that, although there is still room for improvement, POCUS programs have succeeded in many of the goals set forth by the 2015 AAP policy statement, such as establishing and growing an ultrasound curriculum and using various strategies to educate PEM fellows. Abstract : Supplemental digital content is available in the text.